2013
DOI: 10.1117/12.2035516
|View full text |Cite
|
Sign up to set email alerts
|

Local image registration a comparison for bilateral registration mammography

Abstract: Early tumor detection is key in reducing the number of breast cancer death and screening mammography is one of the most widely available and reliable method for early detection. However, it is difficult for the radiologist to process with the same attention each case, due the large amount of images to be read. Computer aided detection (CADe) systems improve tumor detection rate; but the current efficiency of these systems is not yet adequate and the correct interpretation of CADe outputs requires expert human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The left breast mammographic images were mirrored and then registered to their corresponding right breast images. The registration used a standard image registration framework with a B-Spline multiresolution transformation optimizing the Mattes mutual information metric [ 28 , 29 ]. The B-Spline transform T ( x , y ) deforms an image by modifying a mesh of control points which pinpoints to the moving image to maximize of a similarity measure.…”
Section: Methodsmentioning
confidence: 99%
“…The left breast mammographic images were mirrored and then registered to their corresponding right breast images. The registration used a standard image registration framework with a B-Spline multiresolution transformation optimizing the Mattes mutual information metric [ 28 , 29 ]. The B-Spline transform T ( x , y ) deforms an image by modifying a mesh of control points which pinpoints to the moving image to maximize of a similarity measure.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, a series of image transformations are incorporated to enhance different characteristics of the breast in the mammograms. This work is based on and follows previous efforts [30][31][32]. Figure 2 shows how the bilateral asymmetry information was incorporated into the CADx system.…”
Section: Methodsmentioning
confidence: 99%
“…There are many approaches to deal with medical imaging registration, the most recent comparison of algorithms based on a retrospective evaluation was published by West et al [40], but it was constrained to do intrapatient rigid registration. Also recently, Diez et al [28] and Celaya-Padilla et al [30] compared registration algorithms with breast images as a source, and both concluded that the B-Splines approach was the most consistent.…”
Section: Registrationmentioning
confidence: 99%
“…On the other hand, it is important to mention that in this work it was proposed the local image registration method because, according to the work of Celaya et al [42] , where a comparison for bilateral registration mammography was performed, comparing different types of registration in two images that theoretically should present the same characteristics but, due to the biological phenomena, they presented heterogenous tissue, demonstrating that for this type of problem, which is very similar with the problem presented here, the results obtained using this method were the most robust, which allows to confirm the hypothesis that the greater the error in the registry, the greater the deformation in one of the knees.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, the left knee image was reflected and then co-registered with the image of the right knee corresponding. An algorithm of B-Spline multi resolution had the purpose of optimizing the Mattes mutual data measures in the bilateral image registration [29,30] . Then, a deformable B-Spline transform was used, this process based its function in the transformation of an image adjusting control points of a net in base on a similarity measure maximization, this method usually avoids local minimal in the parameter search space and decreases computational time [31,32] .…”
Section: Image Registrationmentioning
confidence: 99%